A Comperative Study on the Influence of Mineral Additives to the Physicomechanical Properties of NHL Mortars Cured in Water - GÜR, DİLARA; Acun Özgünler, Seden (Gazi University, 2021)
This paper focuses on producing a natural hydraulic lime (NHL) mortar with metakaolin, expanded perlite and tuff additives for the purpose of repairing historic masonry. The experimental study was based on laboratory tests for determining the mechanical and physical properties of NHL mortars with mineral additives, under standard and water curing conditions at 7, 28 and 90-day testing periods. Following preliminary tests for selecting most favourable materials; flexural strength, compressive strength, adhesion strength, modulus of elasticity and ultrasound tests were conducted for obtaining mechanical performance. Adhesion strength of mortars were determined by applying each mortar to the most common historic masonry materials. Physical performance of the pozzolan added mortars were investigated through; apparent density, bulk density, water permeability, capillary absorption, water vaporpermeability, porosity tests. Regardless of mineral additive type; water cured mortars reached higher physico-mechanical properties in comparison with the ones cured in relative humidity. Overall, water cured natural hydraulic lime mortars with specific amounts of mineral addition are found promising for the repair of historic masonry.
Keywords: Hydraulic Lime; Mineral Additive; Historic Masonry; Repair Mortar; Water Curing